2009
DOI: 10.1016/s1472-6483(10)60025-9
|View full text |Cite
|
Sign up to set email alerts
|

Over 900 oocyte cryopreservation babies born with no apparent increase in congenital anomalies

Abstract: Over the past decade, the number of reported live births resulting from oocyte cryopreservation has rapidly increased. To appreciate the true number of children born, verified live births were tabulated and assessed. A literature search was performed; authors were then contacted to verify birth outcomes and provide updates. A database including all verified live born infants was constructed. A total of 58 reports (1986-2008) were reviewed, which included 609 live born babies (308 from slow freezing, 289 from v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
228
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(250 citation statements)
references
References 84 publications
8
228
0
14
Order By: Relevance
“…Thus, until recently, cryopreservation of human oocytes was defined as generally inefficient procedure and its application was restricted to the very special situations [29,[34][35][36][37]. The slow freezing remains widely used for oocyte storage but vitrification has progressively emerged as an alternative technique [29,33,[37][38][39][40][41]. This procedure limits the problem of cryoinjury by avoiding ice crystal formation and exerts a less detrimental effect on meiotic spindle [29,33,39,40,42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, until recently, cryopreservation of human oocytes was defined as generally inefficient procedure and its application was restricted to the very special situations [29,[34][35][36][37]. The slow freezing remains widely used for oocyte storage but vitrification has progressively emerged as an alternative technique [29,33,[37][38][39][40][41]. This procedure limits the problem of cryoinjury by avoiding ice crystal formation and exerts a less detrimental effect on meiotic spindle [29,33,39,40,42].…”
Section: Discussionmentioning
confidence: 99%
“…In 2007, SART reported an overall delivery rate per embryo transferred as 30.6% for autologous and 31.7% for donor oocytes in frozen/thawed embryos cycles (SART.org, 2007). Results from series of frozen oocytes (reviewed in ref [32]) compare favorably to these data, especially when one takes into account that in many oocyte thaw studies (those performed by the Italian groups) the number of oocytes that could be thawed and inseminated was limited to three, due to federal statute. If one looks at studies using frozen donor oocytes, the data are even more favorable, with ongoing pregnancy and delivery rates exceeding 50% in some reports [29,[33][34][35].…”
Section: Oocyte Vs Embryo Cryopreservationmentioning
confidence: 94%
“…Chian et al [36] reported on 165 vitrified oocyte pregnancies totaling 200 infants born, and showed no difference in mean birth weight or incidence of congenital anomalies in children born from frozen oocytes vs. those from either spontaneous conception in fertile women, or in women conceiving through fresh IVF. Noyes et al [32] tabulated data from multiple centers around the world using either OC cryopreservation method and found that in 936 babies born from frozen oocytes, there was no apparent increase in the rate of congenital anomalies as compared to United States national statistics for natural conceptions as reported by the CDC. Continued worldwide reporting of healthy live born children from OC will reinforce this trend.…”
Section: Oocyte Cryopreservation Is Not Experimentalmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryopreservation of mature oocytes using vitrification techniques to avoid ice crystal formation has become an effective method to store oocytes, which supports it usefulness for fertility preservation. The technique achieves pregnancy rates close to those of current IVF with fresh oocytes and no apparent increase in congenital abnormalities [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 65%